Modelling and analysis of a PV/wind/diesel hybrid standalone microgrid for rural electrification in Nigeria - Ibim Sofimieari; Mohd Wazir Bin Mustafa; Felix Obite (Institute of Advanced Engineering and Science, 2019)
The scarce electricity supply in Nigeria is a key factor to the low industrial development in a country well-known for having the least electrification in Africa per capita. Presently, Nigeria employs four different kinds of energy such as coal, natural gas, hydro, and oil. Three of the four resources mentioned above used for the production of energy in Nigeria is connected with increasing emissions of greenhouse gas: natural gas, oil, and coal, with coal releasing the worst. This paper presents a model and analysis of PV/Wind/Diesel hybrid system for rural electrification in Kaduna state, northern Nigeria. HOMER (Hybrid Optimization Model for Electric Renewable) software tool was used for optimization and modeling of this work. Simulation results show that the PV/Wind/Diesel system with Battery storage is the most cost-effective system since it recorded considerable cost of energy and reduces CO2 emissions significantly.